New Woman as Seen in Bram Stoker’s Dracula - Rheavanya Winandhini; Rahmawan Jatmiko (Lexicon, 2020)
This paper discusses the influence of feminism in the classic Victorian novel Dracula by Bram Stoker. The New Woman is a feminist ideal that appeared in the 19th century, more specifically amidst the rise of the first wave of feminism. The method of research used in this study covers close reading of the source material and analyzing the characters of the novel through the perspective of the New Woman ideals. The female characters in Bram Stoker’s Dracula portrayed the New Woman characteristic to some degree. Women’s independence, intellect, hyperfemininity, and hypersexuality, are some of the aspects of the movement that go against the norm and values of women in Victorian Britain, such as Mina’s “man’s brain” and Lucy’s hyperfemininity, while the Brides of Dracula provide contrast as the oppressed women with their submissive and compliant attitude towards him. Without erasing their representation of these New Woman ideals, Mina and Lucy also portrayed the complexity and dimensionality of being a woman in the Victorian era; their beauty and appeal were praised while their more “unwomanly” aspects present some threats towards men.